GIS-Based Spatial Patterns Analysis of Airspace Resource Availability in China - Qi Gao; Minghua Hu; Lei Yang; Zheng Zhao (Aerospace, 2022)
Identifying the factors influencing airspace resources, quantifying the availability of airspace resources, and mastering their spatial distribution characteristics are the cornerstone of scientific and efficient airspace management. Therefore, this paper investigates the impact of prohibited, restricted, and dangerous areas (PRDs) on airspace resource availability from a traffic flow perspective, proposes a multi-layer network model, and establishes a flow-based sector resource availability (FSRA) calculation model. The FSRA in mainland China is calculated above the standard pressure altitude of 6000 m. The results show that the FSRA is lower when the sector is determined to have a higher PRD density, a more complex traffic flow pattern, and a more sophisticated interaction between the two. China’s mainland airspace is separated into three altitude ranges along the vertical direction according to the FSRA and sector distribution: 6000–7800 m, 7800–8900 m, and 8900–12,500 m. The spatial distribution characteristics of the FSRA are addressed using the ArcGIS software. The results demonstrate that spatial autocorrelation is exhibited for all three altitude ranges. The high–high cluster pattern mainly occurs in the western part of mainland Chinese airspace, while the low–low cluster pattern is distributed in the southeast. The three altitude ranges are divided into three groups, respectively, and suggestions for airspace management are made for each group.